2015
DOI: 10.1016/j.rbmo.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Paternal obesity negatively affects male fertility and assisted reproduction outcomes: a systematic review and meta-analysis

Abstract: This systematic review investigated the effect of paternal obesity on reproductive potential. Databases searched were Pubmed, Ovid, Web of Science, Scopus, Cinahl and Embase. Papers were critically appraised by two reviewers, and data were extracted using a standardized tool. Outcomes were: likelihood of infertility, embryo development, clinical pregnancy, live birth, pregnancy viability, infant development, sperm; concentration, morphology, motility, volume, DNA fragmentation, chromatin condensation, mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
187
4
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(215 citation statements)
references
References 62 publications
(214 reference statements)
6
187
4
12
Order By: Relevance
“…Moreover, the combination of BMI and age of both men and women had a negative effect on pregnancy rate. A more recent systematic review with thirty papers included [45] confirm these results. Men obesity does not influence conventional sperm parameters but is associated with reduction of live birth rate per cycle and an increase of DNA fragmentation.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, the combination of BMI and age of both men and women had a negative effect on pregnancy rate. A more recent systematic review with thirty papers included [45] confirm these results. Men obesity does not influence conventional sperm parameters but is associated with reduction of live birth rate per cycle and an increase of DNA fragmentation.…”
Section: Discussionmentioning
confidence: 57%
“…Since FertiSTAT was published, more rigorous studies of risks and fertilization in men have been performed (e.g. male obesity; Campbell et al, 2015) and it may be possible to generate a valid male FertiSTAT. Testing feasibility and acceptability would also be necessary because perceptions of male fertility and men's quality of life differ across countries (Sexty et al, 2016), including in the Middle East (Inhorn, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to men, male obesity has been linked to reduced rates of pregnancy and live births (Campbell et al ., 2015). However, studies on specific relationships between semen parameters and obesity have been contradictory.…”
mentioning
confidence: 99%
“…However, studies on specific relationships between semen parameters and obesity have been contradictory. Although different studies have shown correlations between increased obesity and changes in sperm parameters, although selectively (MacDonald et al ., 2010, Sermondade et al ., 2013, Campbell et al ., 2015), others did not report adverse effects (Bandel et al ., 2015). On the other hand, recent studies point to a negative association between body weight and the very integrity of sperm DNA (Fariello et al ., 2012; Taha et al ., 2016); however, these results are not unanimous (Bandel et al , 2015; Campbell et al , 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation